2021
DOI: 10.1002/anie.202100176
|View full text |Cite
|
Sign up to set email alerts
|

Selective Implantation of Diamines for Cooperative Catalysis in Isoreticular Heterometallic Titanium–Organic Frameworks

Abstract: We introduce the first example of isoreticular titanium-organic frameworks,MUV-10 and MUV-12, to show howthe different affinity of hardT i(IV) and soft Ca(II) metal sites can be used to direct selective grafting of amines.T his enables the combination of Lewis acid titanium centers and available -NH 2 sites in two sizeable pores for cooperative cycloaddition of CO 2 to epoxides at room temperature and atmospheric pressure.T he selective grafting of molecules to heterometallic clusters adds up to the pool of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…It was reported that the conversion of epoxides into cyclic carbonates could be effectively improved by increasing the reaction temperature and pressure or prolonging the reaction time. [44][45][46][47] Indeed, although carried out under room temperature and 1 atm pressure, the yields of propylene carbonate and 1,2butylene carbonate by PTC-285 could still be increased to 99% and 95% by prolonging the reaction time to 48 hours (Table 3, entry 1, 3). In addition, the size effect of the substrate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the conversion of epoxides into cyclic carbonates could be effectively improved by increasing the reaction temperature and pressure or prolonging the reaction time. [44][45][46][47] Indeed, although carried out under room temperature and 1 atm pressure, the yields of propylene carbonate and 1,2butylene carbonate by PTC-285 could still be increased to 99% and 95% by prolonging the reaction time to 48 hours (Table 3, entry 1, 3). In addition, the size effect of the substrate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the use of modulators, linker depletion in less often used as a synthetic tool for controlling the formation of defective MOFs. 26,27 We argued the persistent nature of MUV-10 secondary building units, that can be isolated in a broad range of synthetic conditions and are compatible with the assembly of isoreticular frameworks as MUV-12, 28 would be ideal for investigating this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than looking into all the samples available, we decided to analyse in detail the origin of defectivity only for MUV-10 75%, which is the only defective sample that displays a Ti:Ca ratio close to 1. Our compositional analysis [(Ti 2 Ca 2 (µ 3 -O) 2 )(H 2 O) 4 (btc) 2.20 (fa) 0.24 (OH) 1.10 ] 28 though, cannot establish the origin of the defectivity in MUV-10 samples that could equally arise from missing-linker, missing-cluster defects or the coexistence of both. This complex scenario was beautifully illustrated by Liu et al, 15 that demonstrated with HRTEM at subunit-cell resolution the coexistence of different types of defects in UiO-66 crystals with variable populations depending on the synthetic conditions.…”
Section: Fa Ligandsmentioning
confidence: 93%
“…Figure 4 compares IR spectra of the as-prepared and evacuated materials, showing the disappearance of the broad peak associated with the −OH stretch of water. Given prior evidence from CO adsorption studies that water can be removed from the Ti sites of MUV-10(Ca), 65,66 these data suggest MUV-10(M) comprises an unusual family of photoactive MOF with OMSs. Given the ability of MUV-10(M) to stabilize Ti 3+ −H + pairs, we envisioned use of these materials for photoredox transfer hydrogenation catalysis, where bond formation to substrates at photoactive OMS will be beneficial.…”
Section: ■ Results and Analysismentioning
confidence: 67%